A systematic review of the literature on the use of information technologies in supply chain management - Moayad Al-Talib; Walid Al-Saad; Anan Alzoubi; Anthony I. Anosike (International Journal of Industrial Engineering and Operations Management)
Purpose – The purpose of this study is to explore the opportunities provided by information technologies (IT) to improve supply chain processes. It aims to conduct a systematic literature review (SLR) to identify research areas that require further exploration to leverage IT and enhance supply chain performance. Design/methodology/approach – This study employs a systematic literature review methodology to analyse a set of 177 publications, including journal papers, conference papers, periodicals, theses, and books published between 2013 and 2023. Thematic synthesis was chosen as the most appropriate approach to amalgamate the findings obtained from the systematic literature review conducted in the study. This method involves interpreting thematic information and facilitating the development of a comprehensive understanding of the literature being reviewed. Findings – The literature review reveals that certain information technologies, such as the Internet of Things (IoT), Big Data, artificial intelligence (AI), Blockchain, information and communications technology (ICT) and information sharing, offer significant potential for improving supply chain processes. However, the application of these technologies in the field of supply chain is currently under-researched. The findings highlight the need for further exploration of these technologies and their impact on supply chain redesign and enhancement. Originality/value – This study contributes to the existing body of knowledge by providing a systematic overview of the potential benefits of IT in the context of supply chains. It emphasises the under-researched nature of specific technologies and their potential to support organisations in improving their supply chain processes. The originality of this study lies in its comprehensive analysis of relevant literature and its identification of research gaps that need to be addressed in future studies.